Characterization, gene cloning, and heterologous expression of β-mannanase from a thermophilic Bacillus subtilis - Pijug Summpunn (2018)
Bacillus subtilis BCC41051 producing a thermostable β-mannanase was isolated from soybean meal-enriched soil and was unexpectedly found to be thermophilic in nature. The extracellular β-mannanase (ManA) produced was hydrophilic, as it was not precipitated even with ammonium sulfate at 80% saturation. The estimated molecular weight of ManA was 38. 0 kDa by SDS-PAGE with a pi value of 5. 3. Optimal pH and temperature for mannan-hydrolyzing activity was 7. 0 and 60°C, respectively. The enzyme was stable over a pH range of 5. 0-11. 5, and at temperatures of up to 60°C for 30 min, with more than 80% of its activity retained. ManA was strongly inhibited by Hg 2+ (1 mM), but was sensitive to other divalent ions to a lesser degree. The gene of ManA encoded a protein of 362 amino acid residues, with the first 26 residues identified as a signal peptide. High expression of recombinant ManA was achieved in both Escherichia coli BL21 (DE3) (415. 18 U/ml) and B. megaterium UNcat (359 U/ml). © 2011 The Microbiological Society of Korea and Springer-Verlag Berlin Heidelberg.